Trajectories of physical functioning among older adults in the US by race, ethnicity and nativity: Examining the role of working conditions - Pebley, Anne R. (PLoS One, 2021)
Latinos in the US live significantly longer than non-Latino whites, but spend more years disabled. Differentials in socioeconomic status account for part, but not all, of the difference in older age disability between Latinos and whites. We hypothesize that a factor often ignored in the literature—the fact that Latinos, on average, have more physically strenuous jobs than non-Latino whites—contributes to the higher Latino risk of functional limitations at older ages. We use longitudinal data from the 1998–2014 Health and Retirement Study (HRS) comprising 17,297 respondents. Compared to US-born whites, Latinos, especially Latino immigrants, report substantially higher levels of physical effort at work. Latino-black differences are much smaller than Latino-white differences. As hypothesized, physical work effort is strongly related to functional limitations. However, differentials in physical work effort for Latinos and whites in their fifties and early sixties are weakly related to Latino-white differentials in FL at later ages.